PENGARUH PERCEIVED USEFULNESS DAN PERCEIVED SECURITY TERHADAP USE TO E-WALLET DENGAN BEHAVIORAL INTENTION SEBAGAI MEDIASI - Fatimah, Nor Afita Saidah; Negara, Danes Jaya; Sambung, Roby (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2023)
E-wallets are becoming a common means of payment, to replace paper-based instruments with server-based electronic money. This study aims to analyze the use of e-wallets in Indonesia based on an expanded Technological Acceptance Model (TAM), namely perceived usefulness, perceived security, and behavioral intention. The type of data used in this study is primary data, which was collected using an online Google form survey. The sample used in this study was determined by purposive sampling method and obtained 204 respondents, then the data was analyzed using Partial Least Square (PLS) with the SmartPLS 4.0 application. The results of this study found that perceived usefulness and perceived security have a significant effect on behavioral intention. And the behavioral intention mediation variable has a significant effect on actual e-wallet users where the majority of e-wallet users are women with an age range of <26 years (Gen Z) with student status.